Endoscopic closure using an over‐the‐scope clip for pancreatobiliary endoscopy‐related large gastrointestinal perforation (with video). Issue 1 (22nd August 2021) - Fujita, Akashi; Tashima, Tomoaki; Tanisaka, Yuki; Mizuide, Masafumi; Ogawa, Tomoya; Saito, Yoichi; Katsuda, Hiromune; Miyaguchi, Kazuya; Mashimo, Yumi; Nakano, Yuya; Terada, Rie; Jinushi, Ryuhei; et al.
Abstract: Endoscopic ultrasonography (EUS) and endoscopic retrograde cholangiopancreatography (ERCP) for pancreatobiliary diseases require advanced techniques. We usually use an oblique‐viewing endoscope in such procedures. Sometimes, tumor invasion causes gastrointestinal strictures. Crossing a stricture using an oblique‐viewing endoscope is more difficult than using a forward‐viewing scope. Therefore, the frequency of scope perforation is higher than other endoscopic procedures. Although surgical repair for gastrointestinal perforations caused by endoscopes has been performed, patients with pancreatobiliary diseases are often elderly and in poor general condition; therefore, patients are hesitant to undergo surgical treatments. Recently, the usefulness of over‐the‐scope clipping (OTSC) as a minimally invasive rescue method has also been reported. In this study, we report cases of successful endoscopic closure using OTSC for gastrointestinal perforations caused by endoscopes in ERCP and EUS‐related procedures. After those procedures, all cases showed no abnormalities in blood tests or symptoms, and emergency surgery was successfully avoided. Thus, endoscopic closure using OTSC for pancreatobiliary endoscopy‐related gastrointestinal perforations is safe and effective. However, OTSC requires some expertise. A good assessment of defect size and careful insertion of the scope using OTSC attached to the upper esophagus are needed to avoid clip migration or disinsertion and esophageal tears. Therefore, endoscopic closure using OTSC could be the first choice of treatment for pancreatobiliary endoscopy‐related gastrointestinal perforations. We should be familiar with its indication and perform it carefully and rapidly.